Effects of low concentrations of ozone gas exposure on percutaneous oxygen saturation and inflammatory responses in a mouse model of Dermatophagoides farinae-induced asthma - Ohira, Chiharu; Tomita, Kengo; Kaneki, Mao; Iwashita, Naoki; Takagi, Yoshiichi; Kurihara, Takashi; Nagane, Masaki; Kamiie, Junichi; Fukuyama, Tomoki (Archives of Toxicology, 2023)
Ozone gas is widely used in hospitals as well as homes to control COVID-19 infection owing to its cost-effectiveness. Safety standard value and the tolerable value of ozone gas are set at 0.05 ppm and 0.1 ppm, respectively, in developed countries; however, this value was principally determined for healthy individuals, and the risks associated with ozone gas inhalation in patients with pulmonary diseases remains unknown. Recently, we demonstrated that 0.1 ppm ozone gas exposure significantly aggravates the symptoms of acute lung injury in mice. In the present study, we further examined the influence of ≤ 0.1 ppm ozone gas exposure on percutaneous oxygen saturation (SpO 2 ) and pro-inflammatory responses in a mouse model of asthma. Female BALB/c mice were subjected to repetitive intranasal sensitization of Dermatophagoides farinae to generate a mouse model of asthma. Inhalation exposure of ozone gas (0.1, 0.03, 0.01 ppm), generated using an ultraviolet lamp, was performed for five consecutive days immediately before the final sacrifice. There were no abnormal findings in control mice exposed to 0.1 ppm ozone; however, 0.1 ppm ozone exposure significantly reduced the SpO 2 level in asthmatic mice. Histological evaluation and gene expression analysis revealed that pro-inflammatory cytokine levels were significantly increased in mice exposed to 0.1 ppm ozone, indicating that 0.1 ppm ozone exposure affects the development of asthma symptoms. Notably, 0.03 and 0.01 ppm ozone exposure did not have any effects even in asthmatic mice. Our findings indicate that the tolerable level of ozone gas should be adjusted for individuals based on a history of respiratory disorders.